Determination of toxic effects of crude xylanase derived from Thermoascus aurantiacus SL16W by hematology and blood biochemistry in albino rats - Kongbuntad W. (2014)
Xylanase derived from Thermoascus aurantiacus SL16W has characteristics of high activity, heat tolerance and exhibits the potential development for industrial feed enzyme. The objective of this study was to determine the toxic effect of crude xylanase on hematological and blood biochemistry in albino rats. Crude xylanase at doses of 750, 1,500 and 4,000 U kg-1 body weight (bw) were orally administered to rats for 120 days. Hematological and blood biochemistry levels were investigated in two periods (exposure and recovery). It was found that crude xylanase had no effect on rat's body weight. SGOT levels of treated rats significantly decreased as compared to those of control group (p<0.05), while SGPT levels were similar in all groups. BUN levels in treated groups were higher than those of controls in exposure period, but slightly lower in recovery period. However, Creatinine levels in treated groups were not different from control group. It was suggested from the results that crude xylanase is safe for using in animals feed industry. © 2006 Asian Network for Scientific Information.